ORIGINAL BIOTECHNOLOGY OF RECEIVING THE MATRIXES CONTAINING MANNANE AND FUCOIDANE FOR THE PHARMACEUTICAL PURPOSES - Evgenija Vladimirovna Denisova; Inna Vladimirovna Begday; Svetlana Fedorovna Andrusenko; Viktoria Evgen'evna Suprunchuk; Natal'ja Vladimirovna Korablinova; Dar'ja Jur'evna Fofanova (Наука. Инновации. Технологии, 2022)
In article the new technique of receiving the liposomalnykh of matrixes on the basis of polysaccharides as carriers of medicines that is connected frst of all with their low toxicity, a biodegradiruyemost, bioavailability is offered. Strengthening of therapeutic effect, improvement of a pharmacokinetic profle, increase in bioavailability, with simultaneous decrease in side effect of pharmaceutical means, and also increase of chemi-cal and conformational stability allows to create the matrixes differing by the size when using various emulsifers and initiators of polymerization. Mangnang received from 4 types of yeast - from brown seaweed. It is shown that polysaccharides together or separately join in formation of a capsule